Scaredy Squirrel scared silly - Watt, Mélanie, 1975- (Watt, Mélanie, 1975- Scaredy's nutty adventures, 2024)
"Scaredy Squirrel wants a friendly Halloween! His nut tree is bright and cheery, and his costume protects him from anything scary, but will stepping out to trick-or-treat be a nightmare, or will it bring a sweet reward?"--